Penyuluhan Pemamfaatan Bahan Alam Sebagai Biopestisida Kepada Kelompok Tani Desa Negeri Agung, Kecamatan Gunung Pelindung, Kabupaten Lampung Timur - Emantis Rosa; C.N Ekowati; Primasari Pertiwi (CV. Multi Kreasi Media, 2023)
The existence of pests on plants until now can not be avoided. Pests that attack plants can cause decreased production, cause crop failure and can even kill plants and of course this will have an impact on losses to farmers. To deal with pest attacks, farmers usually use chemical insecticides which, apart from being expensive, also have an impact on non-target animals and are not environmentally friendly. Therefore, the use of natural materials as biopesticides is a solution to overcome this problem. However, this is not widely understood by farmers, so counseling is carried out to farmer groups in Negeri Agung Village, Gunung Pelindung District. The results of this community service activity showed an increase in the average knowledge of the participants by 44% from the low category on average (4.5%) to the high category on average (8.9%).